Physiological, Hygienic and Epidemiological Importance of Water (Open Academia: Journal of Scholarly Research, 2024)
On average, 65% (for adults) - 80% (children's body) of the human body consists of water. Water is considered a universal solvent of all substances in the body, and no biochemical process that occurs in the body without water is complete, it is an important component of the cell element, water actively participates in the process of heat management in the body.